A feedforward control for increasing the damping effect of enhanced current-controlled virtual synchronous generator; Electric Power Systems Research; Vol. 234 - Askarov A. B. Alisher Bakhramzhonovich; Ruban N. Yu. Nikolay Yurievich; Bay Yu. D. Yuly Dmitrievich; Ufa R. A. Ruslan Alexandrovich; Malkova Ya. Yu. Yana Yurievna; Suvorov A. A. Aleksey Aleksandrovich (2024, 2024)
Title screen